Total Bakteri Asam Laktat, Aktivitas Antioksidatif, dan Daya Terima Yoghurt Herbal Sinbiotik Jelly Drink Dengan Penambahan Ekstrak Daun Salam - Ninik Rustanti; Nuryanto Nuryanto; Tio Fajarini (Universitas Muhammadiyah Semarang, 2017)
The incidence of metabolic syndrome can be minimized by consuming functional foods and various spices. The sinbiotik herbal jelly yogurt drink with the addition of bay leaf extract can affect the lactic acid bacteria, the antioxidant activity and the level of acceptance of herbal sinbiotik yoghurt jelly drink. The objective of this research is to determine the effect of addition of bay leaf extract to total lactic acid bacteria, antioxidant activity and the level of acceptance of sinbiotik herbal jelly yogurt drink. This was true experimental research with one factor completerandomized design, specifically the addition of indonesian bay leaf extract 0%, 0.13%, 0.3%, and 0.6% in the sinbiotik herbal jelly yoghurt drink. Analysis of total lactic acid bacteria using total plate count test, the antioxidant activity using 1-1-diphenyl-2-picrylhydrazyl test (DPPH), while the acceptance test were analyzed by hedonic test. The addition of bay leaf extract had no significant effect to the total lactic acid bacteria. The highest antioxidant activity on bay leaf extract 0.6% at 49.33%. In the acceptance test give effect to the aroma, color and flavor, butdoes not affect the texture.Keyword :herbal yoghurt, Indonesian bay leave, antioxidant activity, lactic acid bacteria